The role of the church in bridging the gender inequality gap in Malawi through secondary school education : a case of the Livingstonia Synod - Khoswe, Bongani (Stellenbosch : Stellenbosch University, 2023)
Thesis (MTh)--Stellenbosch University, 2023.